Constructing and Co-Constructing Metacognitive Monitoring and Control of 5–7 Year old Children in the Natural Process of Education - Vildžiūnienė, Jelena; Monkevičienė, Ona (Pedagogika, 2023)
The article analyses the construction and co-construction of metacognitive monitoring and control in the natural educational process of 5–7-year-old children. The study was conducted in 27 early childhood education groups by making video recordings of children’s activities during the learning process. The critical incident technique was used for qualitative data analysis. The study revealed the construction and co-construction of metacognitive monitoring (prospective monitoring, goal-oriented action monitoring, activity monitoring) and control (monitoring of the place and conditions of the activity, of the process of the activity, of the overcoming of a challenge or a failure) that children implement in a natural educational process characterised by social interaction. Metacognitive monitoring and control have been found to be constructed and co-constructed when children are acting individually, but side-by-side, in the same activity or task and with the same goal. In this case, children are not only acting, monitoring, and controlling their own action process, but also seeing how others are acting and how they are monitoring and controlling their own activity. Metacognitive monitoring and control are also co-constructed when an activity or task is performed by a group of children working together towards a common goal. In this process, shared monitoring and control take place, the clearer concept of monitoring and control developed jointly in the external plan is transferred to the individual level.